Application of copper nanoparticles containing natural compounds in the treatment of bacterial and fungal diseases. (22nd January 2020) - Hemmati, Saba; Ahany Kamangar, Sheida; Ahmeda, Ahmad; Zangeneh, Mohammad Mahdi; Zangeneh, Akram
Abstract : The development of nanotechnology has generated different nanoscale‐sized materials, with metal‐based nanomaterials being some of the most interesting and promising. Thousands of articles in various specialized journals all over the world are dedicated to different metallic nanomaterials. Metallic nanomaterials are being widely researched, with gold‐, silver‐, iron‐, and copper‐based materials showing potential in medicine. Studies have demonstrated the effect of copper nanoparticles in medicinal herbs on the prevention, control, and treatment of microbial diseases. Experiments have examined the chemical characterization and assessment of the antioxidant, cytotoxicity, antibacterial, and antifungal activities of copper nanoparticles (Cu NPs) using the aqueous extract of Stachys lavandulifolia Vahl flower. These nanoparticles were characterized by UV–visible spectroscopy, field emission scanning electron microscopy (FE‐SEM), energy dispersive X‐ray spectroscopy, transmission electron microscopy (TEM), Fourier‐transform infrared spectroscopy (FT‐IR), and X‐ray diffraction analysis. TEM and FE‐SEM images exhibited a uniform spherical morphology and diameters of 10–25 nm for the biosynthesized nanoparticles. FT‐IR results suggested polysaccharides and protein in S. lavandulifolia acted as reducing agents, reducing copper ions to Cu NPs. In vitro biological experiments indicated that Cu NPs have excellent antioxidant potential against 2, 2‐diphenyl‐1‐picrylhydrazyl, antifungal effects against Candida krusei, Candida parapsilosis, Candida guilliermondii, Candida glabrata, and Candida albicans, and antibacterial activities against Staphylococcus aureus, Enterococcus faecalis, Staphylococcus saprophyticus, Bacillus subtilis, Streptococcus pneumonia, Escherichia coli O157:H7, Salmonella typhimurium, Listeria monocytogenes, Proteus mirabilis, and Pseudomonas aeruginosa . These nanoparticles did not have cytotoxicity properties against human umbilical vein endothelial cells. These results indicate that the inclusion of S. lavandulifolia extract ameliorates the solubility of Cu NPs, which leads to a remarkable enhancement in fungicidal and bactericidal effects under in vitro conditions. Abstract : Application of copper nanoparticles containing natural compounds in the treatment of bacterial and fungal diseases.